The Oxford handbook of managerial economics - Thomas, Christopher R.; Shugart, William F. (New York : Oxford University Press, 2013)
This title comprises 25 chapters contributed by leading scholars in the field who summarize the state of the art in managerial economics and point the way toward future areas of study for students, researchers, and practitioners in all business-related disciplines.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Managerial economics